2018
DOI: 10.1136/bmjopen-2018-021918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity of the selection measures used for the UK’s foundation medical training programme: a national cohort study

Abstract: ObjectivesCurrently relative performance at medical school (educational performance measure (EPM) decile), additional educational achievements and the score on a situational judgement test (SJT) are used to rank applicants to the UK Foundation Years postgraduate medical training programme. We sought to evaluate whether these three measures were predictive of subsequent successful completion of the programme, and thus were valid selection criteria.MethodsData were obtained from the UK Medical Education Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 18 publications
1
45
1
Order By: Relevance
“…A total of 10 were cross-sectional studies, [27][28][29][30][31][32][33][34][35]55 where the outcome was measured at the same time or in the same selection cycle as taking the SJT. A total of 17 were cohort studies 17,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] that had a follow-up period before the outcome of interest was measured. Three studies employed a mixture of F I G U R E 1 PRISMA (preferred reporting items for systematic reviews and meta-analyses) flowchart for the systematic review Abbreviations: CINAHL, Cumulative Index to Nursing and Allied Health Literature; EMBASE, Excerpta Medica Database; ERIC, Educational Resources Information Center; EThos, Electronic Theses Online Service; UCAT, University Clinical Aptitude Test cross-sectional and more distal outcomes.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10 were cross-sectional studies, [27][28][29][30][31][32][33][34][35]55 where the outcome was measured at the same time or in the same selection cycle as taking the SJT. A total of 17 were cohort studies 17,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] that had a follow-up period before the outcome of interest was measured. Three studies employed a mixture of F I G U R E 1 PRISMA (preferred reporting items for systematic reviews and meta-analyses) flowchart for the systematic review Abbreviations: CINAHL, Cumulative Index to Nursing and Allied Health Literature; EMBASE, Excerpta Medica Database; ERIC, Educational Resources Information Center; EThos, Electronic Theses Online Service; UCAT, University Clinical Aptitude Test cross-sectional and more distal outcomes.…”
Section: Re Sultsmentioning
confidence: 99%
“…[52][53][54] The length of followup across the cohort studies varied from 1 to 9 years after taking the SJT. Full details of the included studies are listed in Table S1. A total of 11 studies 17,28,29,35,[40][41][42][43]47,49,50 looked at undergraduate selection for medical school entry, five studies 31,36,37,45,51 at entry to Foundation Year training programmes (the first 2 years of post-qualification training in the United Kingdom [UK]) and 14 studies 27,30,[32][33][34]38,39,44,46,48,[52][53][54][55] at entry to specialty training. The youngest participant mean age was 17.9 years and the oldest was 34.0 years.…”
Section: Re Sultsmentioning
confidence: 99%
“…Therefore, it is more cost-effective than multiple mini interview and selection centers. Despite the use of situational judgment tests for student selection in some health care professions (91)(92)(93)(94)(95), no research evidence was found regarding the use of this method for nursing student selection…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous review of the use of SJTs for the evaluation of non‐academic traits in general concluded that there was evidence of cost‐effectiveness compared to other approaches (eg interviews) . Emerging evidence also indicates that, to date, in a variety of undergraduate and postgraduate medical selection settings, at least modest correlations are observed between performance on these traditional SJTs and subsequent relevant outcomes that reflect aspects of social functioning . This suggests, at least in this context, such selection SJTs are generally estimating, to some extent, knowledge of interpersonal functioning.…”
Section: A Brief History Of Sjts For Personnel Selectionmentioning
confidence: 99%
“…Indeed, there may be little relationship between performance on such instruments and academic achievement in the early years of medical undergraduate education . Evidence for the validity of SJTs in evaluating non‐academic traits for medical selection purposes has also been sought by linking the test scores to outcomes that may require a degree of interpersonal competence, such as performance in high‐fidelity simulations of clinical practice in primary care physicians, successful completion of the first stage of postgraduate medical training or performance in the first year as a general practitioner . Cross‐sectional evidence that supports the concept of SJTs measuring constructs relevant to interpersonal functioning also exists, in the form of correlations with multiple mini‐interviews .…”
Section: Traditional Vs Construct‐driven Sjts: Psychometric Propertiesmentioning
confidence: 99%